Development of CTL-based worksheets to facilitate students’ mathematical critical thinking skills - Taslim, Taslim; Yuanita, Putri; Suanto, Elfis (Universitas Maritim Raja Ali Haji, 2026)
This study was motivated by the low level of students' critical-thinking skills in mathematics. The purpose of this research was to produce a CTL-based student worksheet (LKPD) designed to facilitate students' mathematical critical thinking skills and meet the criteria of validity and practicality. The research used development research, employing the 4-D model, which consists of the define, design, development, and dissemination phases. The study's subjects were Phase D students at SMP Negeri 23 Pekanbaru. The instruments used to measure validity and practicality were validation sheets and practicality questionnaires. The assessment aspects on the validation sheet consisted of face validity, content validity, and construct validity. The overall average validation score was 89.98%, which was categorized as very valid, indicating that the LKPD could be tested after revisions based on the validators' suggestions. Meanwhile, the assessment aspects on the practicality sheet included ease of use, presentation, readability, and time. The practicality test conducted in the small-group trial obtained an average score of 93.11%. Thus, the valid and practical CTL-based LKPD on statistics successfully facilitates Phase D students’ mathematical critical thinking skills, implying its potential as an effective instructional tool for mathematics teachers.